Pregunta
upstudy study bank question image url

\[ \begin{array}{l} =2^{6} \cdot 3^{1} \\ =192 \end{array} \] \[ \begin{array}{l} =\frac{2^{x}(3)}{3.2^{x}} \\ =1 \end{array} \] EXERCISE 1 Simplify the expressions without using a calculator: (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) \( 2 \frac{2\left(2 a^{4}\right)^{3}}{16 a^{12}} \) (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) \( 4 \quad \frac{3 a^{3} \times 5 a^{5}}{\left(5 a^{3}\right)^{2}} \) \( 5 p^{x-1} p^{x+1} \) (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) \( 7 \quad 16^{4 x} \div 4^{2 x} \) (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) 9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) \( 10 \frac{3^{x}+3^{x+1}}{8} \) Negative exponents and the meaning of \( a^{0} \) \( a^{0}=1 \) because \( 5 \div 5=1 \) and \( 5^{1} \div 5^{1}=\frac{5^{1}}{5^{1}}=5^{1-1}=5^{0}=1 \quad \) Using Law 2 For example: \( (2 x)^{0}=1 ; 2 x^{0}=2 \times 1=2 ;(a+b)^{0}=1 \)

Ask by Klein Mccarthy. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

Here are the simplified expressions: 1. \( \frac{4}{5} a^{8} b^{14} \) 2. \( 2 \) 3. \( 3 a^{2} \) 4. \( \frac{3}{5} a^{2} \) 5. \( p^{2x} \) 6. \( -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \) 7. \( 4^{6x} \) 8. \( 8 \cdot 3^{4x - 5} \) 9. \( 2^{1010} \cdot 5^{1011} \) 10. \( \frac{3^{x}}{2} \)

Solución

Let's simplify each expression step by step. ### (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) 1. Multiply the coefficients: \[ \frac{1}{4} \times \frac{16}{5} = \frac{16}{20} = \frac{4}{5} \] 2. Combine the powers of \( a \): \[ a^{5} \times a^{3} = a^{5+3} = a^{8} \] 3. Combine the powers of \( b \): \[ b^{12} \times b^{2} = b^{12+2} = b^{14} \] 4. Final result: \[ \frac{4}{5} a^{8} b^{14} \] ### (2) \( 2 \frac{2(2 a^{4})^{3}}{16 a^{12}} \) 1. Simplify \( (2 a^{4})^{3} \): \[ (2 a^{4})^{3} = 2^{3} a^{12} = 8 a^{12} \] 2. Substitute back into the expression: \[ 2 \frac{2 \cdot 8 a^{12}}{16 a^{12}} = 2 \frac{16 a^{12}}{16 a^{12}} = 2 \cdot 1 = 2 \] ### (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) 1. Combine like terms in the numerator: \[ 6 a^{4} + 9 a^{4} = 15 a^{4} \] 2. Simplify the fraction: \[ \frac{15 a^{4}}{5 a^{2}} = 3 a^{4-2} = 3 a^{2} \] ### (4) \( \frac{3 a^{3} \times 5 a^{5}}{(5 a^{3})^{2}} \) 1. Simplify the numerator: \[ 3 a^{3} \times 5 a^{5} = 15 a^{3+5} = 15 a^{8} \] 2. Simplify the denominator: \[ (5 a^{3})^{2} = 25 a^{6} \] 3. Combine: \[ \frac{15 a^{8}}{25 a^{6}} = \frac{15}{25} a^{8-6} = \frac{3}{5} a^{2} \] ### (5) \( p^{x-1} p^{x+1} \) 1. Combine the powers: \[ p^{(x-1) + (x+1)} = p^{2x} \] ### (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) 1. Expand the square: \[ (-4 a^{2}+b^{3})^{2} = 16 a^{4} - 8 a^{2} b^{3} + b^{6} \] 2. Multiply by \(-2\): \[ -2(16 a^{4} - 8 a^{2} b^{3} + b^{6}) = -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \] ### (7) \( 16^{4 x} \div 4^{2 x} \) 1. Rewrite in terms of base \( 4 \): \[ 16 = 4^{2} \Rightarrow 16^{4x} = (4^{2})^{4x} = 4^{8x} \] 2. Now simplify: \[ \frac{4^{8x}}{4^{2x}} = 4^{8x - 2x} = 4^{6x} \] ### (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) 1. Rewrite in terms of prime factors: \[ 12 = 2^{2} \cdot 3^{1}, \quad 27 = 3^{3}, \quad 18 = 2^{1} \cdot 3^{2} \] 2. Substitute: \[ \frac{(2^{2} \cdot 3^{1})^{x+1} \cdot (3^{3})^{x-2}}{(2^{1} \cdot 3^{2})^{2x-1}} = \frac{2^{2(x+1)} \cdot 3^{x+1 + 3(x-2)}}{2^{2x-1} \cdot 3^{2(2x-1)}} \] 3. Simplify: \[ = \frac{2^{2x+2} \cdot 3^{x+1 + 3x - 6}}{2^{2x-1} \cdot 3^{4x-2}} = \frac{2^{2x+2 - (2x-1)} \cdot 3^{4x - 5}}{1} = 2^{3} \cdot 3^{4x - 5} = 8 \cdot 3^{4x - 5} \] ### (9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) 1. Rewrite \( 10^{1000} \): \[ 10^{1000} = (2 \cdot 5)^{1000} = 2^{1000} \cdot 5^{1000} \] 2. Substitute: \[ \frac{2^{2010} \cdot 5^{2011}}{2^{1000} \cdot 5^{1000}} = 2^{2010 - 1000} \cdot 5^{2011 - 1000} = 2^{1010} \cdot 5^{1011} \] ### (10) \( \frac{3^{x}+3^{x+1}}{8} \) 1. Factor out \( 3^{x} \): \[ = \frac{3^{x}(1 + 3)}{8} = \frac{3^{x} \cdot 4}{8} = \frac{3^{x}}{2} \] ### Summary of

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Mind Expander

If you're curious about how our understanding of exponents has evolved, you'll be fascinated to know that ancient civilizations like the Babylonians had a rudimentary grasp of higher powers and their relationships, laying foundational work that centuries later was formalized by mathematicians such as Blaise Pascal and Leonhard Euler. These greatest minds turned exponential growth into a cornerstone of modern algebra, affecting everything from physics to finance! When tackling those exponent problems, a common pitfall is mismanaging negative and zero exponents—don't forget, situations like \( a^0 \) simplistically mean "one," and \( a^{-n} \) flips into \( \frac{1}{a^n} \). So, channel your inner mathematician: always keep those laws of exponents handy and simplify carefully, ensuring you're following each step without skipping! Happy calculating!

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad